250 Differing risk of ovarian clear cell carcinoma in Asian subpopulations. (13th November 2020) - Chow, S; Kapp, D; Liao, C; Mann, A; Dorigo, O; Litkouhi, B; Darcy, K; Tian, C; Chan, J
Abstract : Introduction: To determine the incidence of clear cell ovarian carcinoma in Asians vs. Whites and within Asian sub-populations. Methods: Data from 2004 to 2016 were obtained from the United States Cancer Statistics (USCS) and National Cancer Database (NCDB). Chi squared tests were used for statistical analyses. Results: Based on USCS, the overall age-adjusted incidence of epithelial ovarian cancer was 11.0 (per 100, 000 women) compared to 0.56 with clear cell histology. Asians had a higher incidence of clear cell cancer compared to Whites (0.97 vs. 0.58). Of 200, 790 women with epithelial ovarian cancer from the NCDB database, the mean age was 57. Asians presented at a younger age compared to Whites (53 vs. 58 years). Of all epithelial cancers, the proportion of clear cell cancer in Whites and Blacks was only 5.2% and 3.2% respectively. However, in the Asian subgroups, the proportion of clear cell histology were significantly higher: 16.6% in Vietnamese, 14.2% Chinese, 13.8% Japanese, 12.9% Filipino, 10.2% Korean, 7.5% Indian/Pakistani, 8.3% Pacific Islander. Geographically, the Northeast region of the U.S. contained the highest proportion of Indian/Pakistanis diagnosed with clear cell. All other Asian sub-populations were more likely to be diagnosed in the Western region. Conclusions: Our data suggested that Asians have a higher incidence of clear cell ovarian carcinoma compared to other races. Moreover, Vietnamese, Chinese, and Japanese demonstrate a higher proportion of clear cell cancer compared to other Asian sub-populations.